Unusually large prostatic utricle cyst - Paudel, K; Kumar, A (Kathmandu University Medical Journal, 2009)
Prostatic utricle cyst is one of the uncommon conditions and only a few cases have been reported. We present a case of unusually large prostatic utricle cyst in a 13- year- old male. He presented with burning urination and post-void dribbling of urine. A cystic mass was felt on digital per rectal examination. Ultrasound pelvis revealed a well-defined midline cystic mass posterior to the urinary bladder. Subsequent magnetic resonance imaging (MRI) of the pelvis demonstrated fluid containing cystic lesion communicating with posterior urethra. Surgical resection of the cyst was performed through the posterior sagittal approach. Follow up of the patient after three months of operation, there was complete resolution of the symptoms. Key words: Prostatic utricle cyst, MRI, Ultrasound doi: 10.3126/kumj.v7i1.1770 Kathmandu University Medical Journal (2009), Vol. 7, No. 1, Issue 25, 73-75